Persons in contexts: the role of social networks and social density for the dynamic regulation of face-to-face interactions in daily life - Roos, Yannick; Krämer, Michael D.; Richter, David; Wrzus, Cornelia (Journal of personality and social psychology, 2024)
Current psychological theories on daily social interactions emphasize individual differences yet are underspecified regarding contextual factors. We aim to extend this research by examining how two context factors shape social interactions in daily life: how many relationships people maintain and how densely people live together. In Study 1, 307 German participants (Mage = 39.44 years, SDage = 14.14) answered up to 20 experience sampling questionnaires regarding their social interactions over 2 days. In Study 2, 313 German participants (Mage = 48.96 years, SDage = 15.54) summarized their daily interactions in daily diaries for 14 days. Participants reported on their social network size and the social density (i.e., household and neighborhood density) of their living situations. Mobile sensing provided additional measures of social interactions and network size. The results showed that participants living in densely populated households transitioned faster from solitude to social interactions but slower from social interactions to solitude. Participants living in dwellings with more homes also transitioned slower from solitude to social interactions. Contrary to the hypothesis, social network size was inconsistently linked with transitions from solitude to social interactions and vice versa. Furthermore, current social desires predicted subsequent social interactions within days, but not across days—irrespective of individuals’ social network size or social density. Together the results point out that people live their daily life in social contexts, which contribute to how they engage in social interactions. The findings thus call for a greater integration of contextual factors in personality theories of social interactions. (PsycInfo Database Record (c) 2024 APA, all rights reserved)